2018
DOI: 10.1016/j.joca.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates intake and its association with changes of periarticular bone area and three-dimensional shape: data from the Osteoarthritis Initiative (OAI)

Abstract: Bisphosphonate intake was associated with a reduction in the odds (approaching but not achieving significance) of expansion periarticular bone area, specifically in the medial tibial sub-region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Furthermore, extensive sensitivity analyses showed conclusions were unchanged when accounting for potential residual confounding, healthy-user bias, or exposure misclassification. This study adds to previous research demonstrating protective effects of bisphosphonates for certain knee OA outcomes, including potential protection from joint space changes (33) and pain outcomes. (11) However, these studies did not take advantage of time-to-event data, instead using hypothesis testing methods to compare JSN (11,33) and pain outcomes.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Furthermore, extensive sensitivity analyses showed conclusions were unchanged when accounting for potential residual confounding, healthy-user bias, or exposure misclassification. This study adds to previous research demonstrating protective effects of bisphosphonates for certain knee OA outcomes, including potential protection from joint space changes (33) and pain outcomes. (11) However, these studies did not take advantage of time-to-event data, instead using hypothesis testing methods to compare JSN (11,33) and pain outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…This study adds to previous research demonstrating protective effects of bisphosphonates for certain knee OA outcomes, including potential protection from joint space changes (33) and pain outcomes. (11) However, these studies did not take advantage of time-to-event data, instead using hypothesis testing methods to compare JSN (11,33) and pain outcomes. (11) Previous work also did not investigate KL progression, which includes a number of osseous features such as osteophytosis and attrition that could reflect bone remodeling of the knee and which may be affected by bisphosphonate effects on subchondral bone.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Subchondral bone includes trabecular bone and the subchondral bone plate, which is corticalized bone similar to that found in other locations. Human osteoarthritis studies using histological and imaging analyses showed that subchondral bone changes are generally characterized by increased bone sclerosis with thickening of the cortical plate, loss of subchondral trabecular rods with thickening of the remaining trabecular bone, alteration in subchondral bone 3-dimensional morphology (27), and formation of new bone at the joint margins (i.e., osteophytes) (28). These changes were detected in late-stage human osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent advances in understanding OA pathogenesis, several DMOAD candidates are currently under investigation. Based on evidence that subchondral bone may play a crucial role in OA progression, drugs such as bisphosphonates, calcitonin and strontium ranelate that can reduce bone resorption and increase bone formation are under consideration [166] [194] [195]. Inflammation and mechanical injury in OA leads to excessive activation of Wnt signaling, which increases transformation of mesenchymal stem cells (MSCs) to bone and induces MMP production, leading to cartilage degeneration.…”
Section: Osteoarthritismentioning
confidence: 99%